Eugenia polyantha (Wight) infusion against oral microorganisms on toothbrushes - Neneng Nurjanah; Eliza Herijulianti; Megananda Hiranya Putri; Susi Sukmasari (Wolters Kluwer Medknow Publications, 2020)
Background: Toothbrushes could get contaminated with pathogenic bacteria from inside or outside the oral cavity. Eugenia polyantha (Wight) has been reported to exhibit antibacterial activity. Objectives: The objective was to assess the potential of E. polyantha infusion to inhibit the growth of oral microorganisms on used toothbrushes. Materials and Methods: Fresh E. polyantha leaves were washed, drained, sliced, boiled in distilled water, and filtered. The filtrate was diluted to 60%, 70%, 80%, 90%, and 100% concentrations with distilled water. Each participant (n = 4) brushed their teeth properly under supervision. The bacterial solution from the used toothbrushes was inoculated into tryptic soy broth (TSB) and incubated. Following this, the bacterial suspension in TSB was evenly inoculated on Muller-Hinton agar plates and incubated. Both the incubations were stored at 37°C for 24 h under aerobic conditions. The diameter of the inhibition zone around the disc containing E. polyantha was measured. Results: The mean diameters of the inhibition zones at 0%, 60%, 70%, 80%, 90%, and 100% concentrations of E. polyantha infusion were 6.10, 13.85, 14.47, 14.61, 15.18, and 15.57 mm, respectively. The inhibition zone at an E. polyantha concentration of 0% statistically significantly differed from those concentrations of 60%, 70%, 80%, 90%, and 100% (P < 0.05 for all). There was no significant difference of measurement growth zone among the different concentrations; there was no inhibition in the control plate. Conclusion: Our results revealed that E. polyantha infusion has the potential to inhibit the growth of oral microorganisms on used toothbrushes; however, this effect is not concentration dependent.